Boendestöd – innebörder och effekter - Andersson, Gunnel; Gustafsson, Hjördis (Socialvetenskaplig tidskrift, 2019)
Social support in independent living for persons with psychiatric disabilities – meanings and impacts Social support in independent living is the most common social intervention for persons with psychiatric disabilities in Sweden. This article investigates what constitutes supportive social support, its meanings and impacts in respect of context, interaction and time. The article emanates from a reanalysis of the results of three user-oriented studies. In total, 56 persons with experience of this type of social support were interviewed. The analytical framework derives from theories of social interaction. The findings reveal that supporting social support is a complex social intervention conveyed through ”the doing”, the talking and the company of the support worker. The findings also show that the restraints of everyday life are allayed or abrogated due to the support: the undoable becomes doable. Finally there are impacts on the psychosocial situation: it contributes to increased well-being and improved psychiatric conditions.